Ethnic discrimination unlearned: experience in the repeated Trust Game reduces trust bias - Duncan, Caitlin; Tölch, Ulf; Walter, Henrik; Dziobek, Isabel (Frontiers in Psychology, 2023)
Discrimination toward ethnic minorities is a persistent societal problem. One reason behind this is a bias in trust: people tend to trust their ingroup and comparatively distrust outgroups. In this study, we investigated whether and how people change their explicit trust bias with respect to ethnicity based on behavioral interactions with in- and outgroup members in a modified Trust Game. Subjects’ initial explicit trust bias disappeared after the game. The change was largest for ingroup members who behaved unfairly, and the reduction of trust bias generalized to a small sample of new in- and outgroup members. Reinforcement learning models showed subjects’ learning was best explained by a model with only one learning rate, indicating that subjects learned from trial outcomes and partner types equally during investment. We conclude that subjects can reduce bias through simple learning, in particular by learning that ingroup members can behave unfairly.